(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Artificial bone implants are used when a bone defect exceeds a critical size, and autografts or allografts are not an option due to insufficient quality or limited availability. Implants must be biocompatible, osteoconductive, ideally bioresorbable, and resistant to mechanical stress during handling and healing [1]. Natural bone is not a homogeneous material but consists of several hierarchically structured phases that cannot necessarily be imitated by one single material. Our approach was therefore to combine two bioceramic materials in one hybrid implant. We used yttria-stabilized zirconia for phases with high mechanical strength and hydroxyapatite for phases that require osteointegration. As a manufacturing process, we used lithography-based ceramic manufacturing to produce the individual green parts (composite material consisting of photopolymer matrix and ceramic powder) which were combined in a sinter-joining process during thermal post-processing. The sinter-joining concept involves inducing a press-fit between the two parts by precisely controlling the shrinking behavior [2]. To establish process control, we started with a simple ring-in-ring design and progressed to biaxial bending plates to quantify mechanical resistance. We found a significant increase in the maximal measured force in the piston-on-three-balls test set-up from (72 ± 53) N to (366 ± 88) N for a 5% and 10% press-fit, respectively. For further evaluation, we created micrographs and assessed shrinking behavior and deformation. As final step, we designed more complex structures to demonstrate the successful sinter-joining. [3] This study demonstrated a proof-of-concept for sinter-joining different bioceramics to create hybrid implants that mimic the multi-phase composition of natural bone by combining bioactive with mechanically strong materials. We have published this study in the Open Ceramics Journal [3]. References [1] V. Campana et al., “Bone substitutes in orthopaedic surgery: from basic science to clinical practice,” J Mater Sci: Mater Med, vol. 25, no. 10, pp. 2445–2461, Oct. 2014, doi: 10.1007/s10856-014-5240-2. [2] J. Schubert, Y. End, V. Schulze, and F. Zanger, “Exploring the Applicability of Sinterjoining to Combine Additively Manufactured Ceramic Components,” Procedia CIRP, vol. 115, pp. 18–23, 2022, doi: 10.1016/j.procir.2022.10.043. [3] S. Nistler, C. Hofstetter, S. Baudis, M. Schwentenwein, and J. Stampfl, “Sinter-joining of two different bioceramic materials,” Open Ceramics, vol. 22, p. 100759, Jun. 2025, doi: 10.1016/j.oceram.2025.100759.